Desenvolvimento e aplicação de um sistema para controle de manutenção em uma empresa de locação de máquinas de construção - Sena, Matheus Chrystian Gois (Universidade Federal Rural do Semi-Árido, 2020)
One of the main concerns of companies that have construction machinery and equipment is the maintenance area. This sector must ensure the availability of machinery, vehicles and equipment when needed. In this context, this paper aims to present a maintenance monitoring and control model and the implementation in a company that sells, leases and maintains construction equipment in Mossoró-RN. The company's concern in this sector is due to the harsh working conditions of the equipment, some even working three shifts every day of the week. Such working conditions result in several stops for corrective maintenance, better maintenance control aims at creating a preventive maintenance plan so that fewer corrective maintenance stops occur as it is more expensive and commonly leaves equipment unavailable. for several days. After an initial follow-up on its current maintenance process, it was decided in conjunction with the company's management that a maintenance plan for the equipment would be defined, acting in a preventive and predictive manner, seeking to reduce the number of failures that lead to unscheduled downtime.
Keywords: Manutenção; equipamentos de construção; preventiva; corretiva; ENGENHARIAS::ENGENHARIA MECANICA